’THE SECOND REPUBLIC’ - DOES THE REPUBLIC OF SRPSKA NEED A NEW CONSTITUTION? - Savanović, Aleksandar (Politeia, 2021)
In this paper, we will try to suggest the possibility of a new constitution of the Republic of Srpska. By that political act, the ’Second Republic’ might be created. With this in mind, our approach has two steps. The first one is negative: it should explain that in the Constitution of the Republic of Srpska there are some deficiencies, both formal and substantial. The second step is positive: it suggests a direction that has to be taken in the process of creation of our new Constitution. Our basic assumption is that the current Constitution of the Republic of Srpska cannot provide effective framework for our political community. In fact, our current constitution is one of the main sources of problems and conflicts in our political community. This diagnosis is quite opposite to the main line of understanding of the crisis in Bosnia and Herzegovina and the Republic of Srpska respectively: the standard perception of the former and the latter is that there is some kind of deficiency as regards the Constitution of Bosnia and Herzegovina. Yet, it is the constitutions of the entities of the Republic of Srpska and the Federation of Bosnia and Herzegovina that are almost never discussed.
Keywords: Republic of Srpska; Constitution; Second Republic